ANALYSIS OF INDICATORS OF THE ACTIVITIES OF ORGANIZATIONS IN THE IMPLEMENTATION OF M&A TRANSACTIONS IN THE IT SPHERE - Schneider, O.V; Sharmandzhieva, G.S (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The development of mergers and acquisitions (M&A transactions) as a factor of the growth and expansion of the company has led to need for a properly structured and correctly carried out pre-investment research. The results of research affect both the price of the deal and the probability of its implementation. Conducting a qualitative research is a rather labor-intensive process, the effectiveness of which is significantly reduced in the absence of a clearly structured system of analysis of performance indicators. Quantity of transactions, as well as the basis of the increase in value terms, mainly relates to two areas - oil and gas and IT. At the same time, according to KPMG analysis, the desire of major players in the innovation and technology sector to create an ecosystem for the consumer (taxi services, food delivery and other services to meet human needs by one company or Group of Companies) is increasingly shifting the focus from studying basic financial indicators. The focus of investors are: the uniqueness of the proposed product, the professionalism of the team servicing and supporting the product, the operating model and operational indicators. However, the focus shift is not accompanied by the development of the Russian methodological base in relation to the analysis of operational indicators, which is currently very limited, therefore, this article proposes to consider their key metrics. For the analysis of financial indicators, various methods are proposed, mainly using the coefficient method, which has some disadvantages, including the non-adaptation of the recommended values to industry specifics. The indicated limitations of the methodological base in relation to operational indicators, as well as the unresolved drawbacks of financial analysis techniques, necessitate further scientific research.